2012
DOI: 10.1007/s00221-012-3137-1
|View full text |Cite
|
Sign up to set email alerts
|

Training-related decrease in antagonist muscles activation is associated with increased motor cortex activation: evidence of central mechanisms for control of antagonist muscles

Abstract: During human contraction, net joint torque production involves the contribution of the antagonist muscles. Their activation protects the articulations and facilitates movement accuracy, but despite these fundamental roles, little is known about the brain mechanisms underlying their control. In view of previous studies that showed lesser antagonist muscles activation in participants engaged in regular strength training (ST) than in participants actively engaged in endurance disciplines (ED), we used this betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
4
15
0
2
Order By: Relevance
“…The net torque corresponds to the sum of the individual torques developed by the muscles and other structures crossing the joint (Zajac et al, 2002). Antagonist muscles, acting in the opposite http direction to the net torque, have an important functional role in movement coordination and accuracy (Gribble et al, 2003;Rao et al, 2009;Wiegner, 1992, 1996), joint stiffness and stability Kellis, 1998;Kellis and Baltzopoulos, 1997;Lestienne, 1979;Solomonow et al, 1988), and effective net torque production (Dal Maso et al, 2012;Häkkinen et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…The net torque corresponds to the sum of the individual torques developed by the muscles and other structures crossing the joint (Zajac et al, 2002). Antagonist muscles, acting in the opposite http direction to the net torque, have an important functional role in movement coordination and accuracy (Gribble et al, 2003;Rao et al, 2009;Wiegner, 1992, 1996), joint stiffness and stability Kellis, 1998;Kellis and Baltzopoulos, 1997;Lestienne, 1979;Solomonow et al, 1988), and effective net torque production (Dal Maso et al, 2012;Häkkinen et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Dal Maso et al . () suggested that the cortical oscillations ~ 20 Hz recorded over the M1 might have a critical role in the modulation of antagonist muscle activations. The decrease in the magnitude of the CMC ~ 10 and ~ 20 Hz with the force level could thus reflect a functional neurophysiological mechanism that would take part in the control of the exerted force by modulating agonist and antagonist muscle activations.…”
Section: Discussionmentioning
confidence: 70%
“…Prior the experimental session, participants performed 3 so‐called relative Maximum Voluntary Contractions (rMVC) around the right elbow joint in flexion. The rMVC was determined as the highest net moment reached while keeping at rest all the muscles not involved in the task, especially face and neck muscles, to avoid muscles artifact in EEG recordings (Dal Maso et al ., ; Cremoux et al ., ,b). The experimental protocol consisted of 21 elbow isometric flexion contractions at 25, 50 and 75% rMVC randomized in seven sets of contractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation in net joint torque stability could result from an altered control of the activation of agonist and antagonist muscles, respectively, acting in the direction or in the opposite direction of the net joint torque (Basmajian, ). Recent studies showed the involvement of the primary motor cortex (M1) in the regulation of agonist and antagonist muscle activations with the force level (Cremoux, Tallet, Dal Maso, Berton, & Amarantini, ; Dal Maso, Longcamp, & Amarantini, ; Dal Maso, Longcamp, Cremoux, & Amarantini, ). However, M1 involvement in the regulation of agonist and antagonist muscle activations with the phases of contraction remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%